Sex role behavioral differences in parental alienation - Chen, Qi, author; Ratajack, Ellen, author; Harman, Jennifer, author (Colorado State University. Libraries, 2016)
Men and women deal with conflicts in different ways and sex differences have been demonstrated in terms of aggressive behaviors. The purpose of the current study is to examine if gender differences exist in the context of divorce, particularly when children are involved when parental alienation occurs. We hypothesized that men are more likely to use direct aggression to prevent a mother from seeing her children while women would employ more indirect aggression to assist with the alienation.
Keywords: aggression; aggressors; parental alienation